Pembelajaran Praktis Pembuatan Jepit Rambut dari Kawat Bulu sebagai Upaya Peningkatan Kreativitas Mahasiswa - Amanah Rahmadhani; Anggit Dyah Kususmastuti (Lembaga Pengembangan Kinerja Dosen, 2025)
In the Business Administration study program, the development of student creativity is often limited to theory, without providing enough space to practice directly making creative products. This causes the development of student creativity which is actually very important in the business world to be less than optimal. To overcome this problem, this activity aims to improve the creativity of 4th semester Business Administration students who take the creativity and innovation course through practical learning of making hair clips from wire feathers. The method of this activity includes the stages of planning, implementing activities, evaluation, and documentation. The results of this activity show a significant increase in creativity, technical skills, and entrepreneurial spirit of students. The output of the activity is a hair clip made by students from wire feathers, which has economic and aesthetic value. This activity has succeeded in providing a useful experience that improves students' abilities in creativity and entrepreneurship and fosters a desire to become entrepreneurs sustainably.